Ethnic diversity and the control of natural resources in Southeast Asia (Center for South and Southeast Asian Studies, University of Michigan, 1988)
Contents: Ethnic groups and the control of natural resources in Kelantan, Malaysia; ethnic concentrations; changing ethnicity and social resources in a Thai-Mon village.